Role of Emotional Intelligence in Leadership Effectiveness in Rwanda - Aimee, David (American Journal of Leadership and Governance, 2024)
Purpose: The aim of the study was to assess the role of emotional intelligence in leadership effectiveness in Rwanda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Emotional intelligence (EI) significantly impacts leadership effectiveness by enhancing leaders' ability to manage their own emotions and understand and influence the emotions of others. Leaders with high EI demonstrate greater empathy, enabling them to build stronger relationships and foster a positive organizational climate. They excel in communication, conflict resolution, and decision-making, which are crucial for team cohesion and performance. EI contributes to resilience, allowing leaders to navigate stress and setbacks effectively. Moreover, emotionally intelligent leaders inspire and motivate their teams, driving higher engagement and productivity. Overall, EI is a critical component for achieving successful leadership outcomes. Implications to Theory, Practice and Policy: Trait theory of leadership, contingency theory and transformational leadership theory may be used to anchor future studies on assessing the role of emotional intelligence in leadership effectiveness in Rwanda. In terms of practical applications, organizations should integrate EI assessments and development programs into their leadership training and development initiatives. On the policy front, it is important to advocate for the inclusion of EI education in leadership curricula at educational institutions.